2016
DOI: 10.1161/circresaha.116.307972
|View full text |Cite
|
Sign up to set email alerts
|

Transcathether Valve Replacement and Valve Repair

Abstract: Transcatheter aortic valve replacement for treatment of aortic stenosis has now become an accepted alternative to surgical valve replacement for some patients. In addition, transcatheter mitral valve repair is also routinely used in high surgical risk patients with mitral regurgitation. Other transcatheter procedures are in rapid development. The current review attempts to summarize the procedures and echocardiographic imaging used for transcatheter valve replacement or valve repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 136 publications
(133 reference statements)
0
15
0
1
Order By: Relevance
“…Transcatheter tricuspid procedures are guided by 2D and realtime 3D TEE in combination with fluoroscopy, which enables precise positioning of catheters and implants. Near-field views of the TV are obtained using deep transesophageal and transgastric positions of the TEE probe (101). A good acoustic transgastric short axis window is essential to ensure procedural feasibility.…”
Section: Procedural Guidingmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcatheter tricuspid procedures are guided by 2D and realtime 3D TEE in combination with fluoroscopy, which enables precise positioning of catheters and implants. Near-field views of the TV are obtained using deep transesophageal and transgastric positions of the TEE probe (101). A good acoustic transgastric short axis window is essential to ensure procedural feasibility.…”
Section: Procedural Guidingmentioning
confidence: 99%
“…Fusion-imaging integrating echocardiography and/or MSCT, and fluoroscopy require further validation for tricuspid interventions. However, it has the potential to simplify the procedural steps through sophisticated visualization of anatomical structures and catheters/devices in relationship to each other (101,106,110).…”
Section: Adjunctive Imaging and Visualization Techniquesmentioning
confidence: 99%
“…Die beiden aktuell publizierten, randomisierten Studien COAPT und MITRA-FR haben auf den ersten Reduktion der MI, ohne durch eine Verkleinerung der Mitralklappenöffnungsfläche (MKÖF) eine hämodynamisch relevante Mitralklappenstenose zu erzeugen [1,5]. Ähnlich wie bei der primären MI gelten die oben genannten Kriterien auch für das Clipping einer sekundären MI, um ein sicheres Greifen und Inserieren der Segel in den Clip zu ermöglichen.…”
Section: Interventionelle Echokardiografieunclassified
“…A recent paper studying treatment of degenerative MR suggested that higher baseline left-ventricular end-diastolic diameter and mitral annular diameter predict greater than mild residual MR after mitraclip (17). In current clinical practice, absolute anatomic limitations are very few (18). Hahn et al listed the echocardiographic features associated with ideal, challenging and difficult anatomies (Table 2) (18).…”
Section: Mitraclipmentioning
confidence: 99%